If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x+2)2=3x^2+6x+4
We move all terms to the left:
(3x+2)2-(3x^2+6x+4)=0
We multiply parentheses
6x-(3x^2+6x+4)+4=0
We get rid of parentheses
-3x^2+6x-6x-4+4=0
We add all the numbers together, and all the variables
-3x^2=0
a = -3; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·(-3)·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:$x=\frac{-b}{2a}=\frac{0}{-6}=0$
| -11=t-10 | | 2/3x+2/6=-1 | | (5+x)×(x+7)×(10+x)=0 | | 50–18x=(18x–2)+10–(8x+2) | | 16x+17=12x-21 | | 3/5(x+(1/3))=14/5 | | 7x/4-34=15 | | 112x–75=800+12x | | 9/4=m/2 | | 15+9x-7x+14=7 | | (q-10)×3=6q= | | (7c-7)+(6c-8)=180 | | (2x-8)+(3x+3)=180 | | (6d+4)+62=180 | | (6a-8)+50=90 | | 20=8x-12* | | 45=4x+x+10* | | 40+14y=–20–8y–6 | | 7y+6=275 | | 0,96−2,4x=7,2 | | 3(3-2x)=2x+11 | | x-0.61x=4054127 | | 7x-6-4x+3=15 | | -2/5-y/3=1/15 | | x-12=74 | | 〖4x〗^(-4)-〖5x〗^(-2)+1=0 | | 3x−2,2=6,8 | | (5x+15)-(8x+40)=(x-65) | | 2x+x+x–16=x+8x | | 4x/9=8/27 | | x+3,5=4,7 | | x−13=290 |